Risk Management Implementation in Primary Health Care Quality Improvement: A Qualitative Case Study at Siriwo Community Health Center - Angelia Adii; Merlince Kedepa; Ana Zakiyah (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Primary health care plays a vital role in ensuring equitable access to essential health services; however, quality and patient safety gaps remain significant, particularly in resource-limited settings. Risk management is recognized as a governance strategy for reducing preventable harm and improving service quality, yet its implementation at the facility level is often inconsistent. Objectives: This study aimed to examine how risk management was implemented and its contribution to improving service quality at Siriwo Primary Health Care in Indonesia. Methods: A qualitative single-case study design was conducted. Participants included the health center director, quality improvement officers, health professionals, and administrative staff with at least 1 year of experience. Data were collected through in-depth semi-structured interviews, non-participant observations, and document reviews. All interviews were audio-recorded and transcribed verbatim. Data were analyzed thematically using coding, categorization, and theme development. Triangulation across data sources was applied to enhance credibility and rigor. Results: Risk management was implemented progressively through risk identification, assessment, and control integrated into routine service activities. Key risks included patient safety incidents, service delays, procedural errors, supply limitations, and human resource constraints. The implementation strengthened adherence to standard operating procedures, improved internal monitoring, enhanced staff awareness of patient safety, reduced the recurrence of complaints, and increased perceived community satisfaction. Conclusions: Integrating structured risk management into daily operations improved service quality and fostered a stronger patient safety culture. Context-adapted risk governance may be an effective strategy for enhancing primary health care performance in resource-limited settings.